Factors Influencing the Effectiveness of MICP in Dispersive Soil Improvement: A Review - Liu, Tiantian; Yuan, Xiaoqing; Wang, Xi (Journal of Progress in Civil Engineering, 2025)
Microbially Induced Calcite Precipitation (MICP) technology has demonstrated significant potential in the improvement and stabilization of dispersive soils due to its environmental friendliness, efficiency, and cost-effectiveness. Dispersive soils, characterized by high exchangeable sodium ion content, are prone to dispersion upon contact with water, leading to severe soil erosion and structural instability. Traditional improvement methods, such as the use of chemical additives and industrial by-products, are often associated with environmental pollution and high costs. MICP, through the catalytic activity of urease in bacteria, generates calcium carbonate precipitates, which enhance the cementation between soil particles, thereby improving the soil's mechanical strength and stability. This review summarizes the key factors influencing MICP effectiveness, including the pH and concentration of the cementation solution, as well as curing time, and systematically evaluates how these factors impact the dispersivity and strength of dispersive soils. Studies show that optimal conditions for soil improvement are a pH range of 7-8, a cementation solution concentration of 1.0 mol/L, and a curing time between 7 and 14 days. Furthermore, there is a positive correlation between calcium carbonate content and soil strength; however, excessive calcium carbonate precipitation can increase soil brittleness, potentially leading to performance degradation. Through a systematic analysis of the mechanisms underlying these factors, this paper proposes methods to optimize MICP technology for soil stabilization, emphasizing the importance of further research on the interactions between these factors and their long-term effects to enhance the application efficiency and sustainability of MICP in practical engineering.